Crossings : early Mediterranean contacts with India - De Romanis, Federico; Tchernia, André.; France. Ambassade (India). Centre for Human Sciences; Italy. Ambasciata (India). Cultural Centre (New Delhi : Manohar Publishers & Distributors, 1997)
Collection of articles translated from French and Italian.
"Centre De Sciences Humaines, New Delhi, Italian Embassy Cultural Centre, New Delhi."
Errata slip inserted.
Includes bibliographical references (p. [277]-283).
Includes passages in Sanskrit, Greek, and Latin.
Keywords: India -- Relations -- Rome; Sri Lanka -- Relations -- India; Sri Lanka -- Relations -- Rome; Rome -- Relations -- Sri Lanka